Development of Electric Vehicles and its Role in the Iranian Automobile Part Industry - Mohammad Moghbeli , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research mainly aims to investigate the role of the development of electric vehicles in the Iranian automobile part industry. In terms of purpose, this research is an applied study and in terms of method, it is a descriptive-survey and exploratory research. The population includes all the companies working in electric vehicle industry (including the manufacturers and importers). According to studies, 121 companies work in this area. Out of the mentioned population, 50 companies were selected as the samples by snowball sampling and theoretical saturation. Data analysis was done by descriptive statistics and thematic analysis. The results showed that the production of electric vehicles is not still at a proper situation and this condition should be improved by developing and legal and financial infrastructures. So, it can be concluded that mass production of electric vehicles in the country has not been realized yet and this industry is still developing. Hence, automobile part manufacturing industry does not have a proper situation.